Nonstoichiometric copper chalcogenides for photo-activated alkyne/azide cycloaddition. Issue 10 (28th February 2017) - Zou, Hong Yan; Gao, Ming Xuan; Yang, Tong; Zeng, Qiao Ling; Yang, Xiao Xi; Liu, Feng; Swihart, Mark T.; Li, Na; Huang, Cheng Zhi
Abstract : Cu(i ) present in nonstoichiometric copper chalcogenides and associated with copper vacancy defects is released under illumination, enabling efficient photo-activated catalysis of azide–alkyne cycloaddition reactions. Abstract : Nonstoichiometric copper chalcogenides with heavy copper vacancies can be used as an effective photo-activated catalyst for the Huisgen [3+2] cycloaddition reaction as Cu(i ) can be released corresponding to holes (Cu-defects) under light irradiation. These strategies expand new possibilities for carrying out prototypical click chemistry in the presence of functional groups.